Tecnologia para monitoramento da temperatura do leite cru refrigerado durante o transporte para melhoria de ecoeficiência - Ferreira, Mariane Bigarelli (2021)
The dairy sector has stood out for the constant increase in productivity in Brazil, with strict quality controls, supported by rules and laws. The main challenges encountered in the milk production process are related to quality problems during the transport of refrigerated raw milk, carried out by tank trucks from rural properties to the milk processing industries. These problems involve failures in monitoring the temperature of the milk during transport, compromising the quality of the product, generating increased costs and potential environmental impacts, due to the need to dispose of the cargo. In this sense, this study aims to provide a technological solution to improve eco-efficiency in monitoring the temperature of refrigerated raw milk during transport. The proposed technology is presented as a Portable Device to Measure, Read and Manage the Temperature of Liquids During Transport (Patent Deposit: BR102019021479). To validate the use of the proposed technology, a market survey was carried out. This portable device allows the detection and monitoring of the temperature of chilled raw milk, storing the temperature data collected automatically, allowing the management of the temperature, in order to avoid its disposal and waste. To validate the use of the proposed technology, a market survey was conducted, in which five companies in the national sector reported the need to obtain a device for reading and managing the temperature of raw milk during transport, since four of these companies show losses in the product due to milk quality problems resulting from temperature variations. In view of the waste generated, an eco-efficiency study was carried out, based on the application of the Life Cycle Assessment technique. To this end, two study scenarios were established, the first in which raw milk is not discarded when it reaches the milk processing industry, and the second, where raw milk be discarded. Through this study, it was concluded that the use of the proposed technology allows an annual eco-efficiency gain of up to 0.0123%. Even so, the gains successfully reach the need of the companies involved in the sector, in meeting the technical regulation of chilled raw milk (IN 76/2018), it also allows companies to act in a preventive way against possible damage to the quality of the cargo, since it allows the construction of a database, where its analysis can generate knowledge of important information for possible investigations of problems involving the collection and transport of milk.